Knowledge and Adoption Level of Dairy Farmers about Bovine Ectoparasites in the Operational Area of Dairy Vigyan Kendra, Vejalpur, Gujarat (India) - Jadav, Sanjay (Indian Journal of Dairy Science, 2020)
The study was emphasized on knowledge and adoption level of dairy farmers about bovine ectoparasites in the operational area of Dairy Vigyan Kendra (DVK), Vejalpur, Gujarat (India). Using the simple random sampling method, 300 respondents from 30 villages of 10 talukas in the operational area of Dairy Vigyan Kendra, Vejalpur were selected. Majority of dairy farmers (80.33%) reported that their animals were suffering from ticks during study period 2019-20. An arrangement of major components of dairy farmers’ knowledge level about bovine ectoparasites as ‘Symptoms of animal → Prevention & Control of ectoparasite infestation → Transmission → General information → Various diseases transmitted due to ectoparasites’ were ordered in decreasing trend. The majority of dairy farmers (74.67%) had medium level of knowledge about bovine ectoparasites. Dairy farmers (37.67 %) had low adoption level regarding the practices of bovine ectoparasites’ control. Correlation between knowledge level and adoption level of dairy farmer regarding bovine ectoparasites was found to be highly significance at 0.01 level of significance.